Physiological and Chemical Changes During Harvest Maturity in Apple Cultivars - Gercekcioglu, Resul; Cekic, Cetin; Filiz, Ali (Asian Journal of Chemistry, 2016)
Experiments were conducted in 2002 and 2003 with ‘Kasel 37 (Amasya)’, ‘Starkrimson Delicious’ and ‘Stark Spur Golden Delicious’ apples. The optimum picking period for longterm shelf life corresponds to the period at which the respiratory activity of fruits is minimum or slightly late in climacteric fruits. However, slightly late period is the more reliable date for harvesting. Respiration rates were found 12.92 and 17.13 for Amasya, 17.52 and 19.44 for Starkspur Golden Delicious, 14.33 and 16.33 mL CO2/kg h for Starkrimson Delicious. On the other hand, at the maturing date, several chemical and physiological changes were also observed which are suitable for optimum harvest criterion. The criteria like ground colour, flesh colour, flesh firmness, total solid soluble, maturity ratio and sensory analyses scores were observed for all cultivars.